Bridging Policy and Practice: Local Content Curriculum, Cina Benteng Culture, and Buddhist Values in an Indonesian Elementary School - Sabar Marjoko; Sutadi (MIMBAR PGSD Undiksha, 2026)
The gap between local-content curriculum policies and their implementation has limited the strengthening of cultural identity, character development, and graduate quality. Local cultural and religious values have also not been systematically integrated into instructional design and practice. This study aimed to analyze the development, implementation, challenges, and impacts of the local content curriculum on student competencies and graduate quality. This research employed a qualitative approach with an intrinsic case study design. Data were collected through interviews, observations, and documentation, while questionnaires were used as supporting data to enrich qualitative findings. Data analysis was conducted using the interactive model with source and technique triangulation to ensure data credibility. The findings reveal that local content curriculum development remains predominantly top-down and has not been fully aligned with regulatory mandates and socio cultural contexts. Curriculum implementation has not optimally integrated local cultural values and Buddhist teachings into learning planning, implementation, and evaluation. The main challenges include limited teacher competence, insufficient learning resources, and gaps in understanding curriculum regulations. This study concludes that contextual curriculum repositioning, strengthening curriculum design, enhancing teacher capacity, and integrating cultural values are essential strategies to develop a local content curriculum that supports global competencies while preserving local identity and character development. The findings imply that sustainable collaboration among educational stakeholders is required to create a more relevant, adaptive, and culturally responsive curriculum framework.